Strategi Dakwah Salafidi Era Digital:Kajian Literatur Terhadap Pendekatan Dan Media Dakwah - Ummu Azka Amalia (AT-TAWASUL, 2024)
This research examines Salafi da'wah strategies in the digital era with a focus on the approach and media used. In the digital era, information and communication technology has a very useful position in people's lives. With 185 million internet users in Indonesia, da'wah through digital media is becoming increasingly relevant. This research includes qualitative research using a descriptive approach, utilizing literature studies from various previous literature and journals. The results and discussion in the research state that the use of social media such as Instagram and YouTube by Salafi figures, such as Khalid Basalamah, has succeeded in attracting the attention of a wide audience. Da'wah through digital media allows the spread of Islamic teachings more effectively and efficiently. In conclusion, digital technology provides great opportunities for the spread of Salafi da'wah in Indonesia.